The role and impact of artificial intelligence in modern education: analysis of problems and prospects - Iasechko, Svitlana; Iasechko, Maksym (Review of Artificial Intelligence in Education, 2024)
The main hypothesis of the study is that the use of elements of artificial intelligence can have a positive effect on the quality of the educational process in higher education institutions, provided that three main conditions are met: access to the necessary data, training of future teachers to work with artificial intelligence and the creation of a special educational course. Within this study, the following tasks were set: to analyze scientific and methodological research aimed at studying the current state, prospects and possibilities of using artificial intelligence in the training of future teachers of professional education; to analyze how intelligent expert systems are distributed in the educational field; consider the necessary pedagogical conditions for the successful implementation and use of a system with elements of artificial intelligence in the educational process of higher educational institutions.